2006
DOI: 10.1111/j.1528-3585.2006.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing an International System for Internally Displaced Persons

Abstract: A pressing new problem came onto the international agenda at the end of the cold war, persons forced from their homes by conflict and human rights violations who remain uprooted and at risk within the borders of their own countries. The international system created after the Second World War to protect and assist refugees, people who flee across borders, did not extend to internally displaced persons (IDPs). Over the past fifteen years, substantial efforts have been made to create an international system to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…As also noted by other investigators the women in our study were more impoverished when their husbands died or migrated to different locations within Ghana in search of employment (Cohen 2006;Martin 2004). Respondents reported that men who left in search of employment often abandoned their displaced families in order to establish a new family in one of the urban areas in the south.…”
Section: Study 1: Ethnic Conflict Older Women and Family Survival Insupporting
confidence: 53%
“…As also noted by other investigators the women in our study were more impoverished when their husbands died or migrated to different locations within Ghana in search of employment (Cohen 2006;Martin 2004). Respondents reported that men who left in search of employment often abandoned their displaced families in order to establish a new family in one of the urban areas in the south.…”
Section: Study 1: Ethnic Conflict Older Women and Family Survival Insupporting
confidence: 53%
“…Since the 1990s, the category of Internally Displaced Persons (IDPs) has become a subject of considerable debate and concern. (Cohen 2006;Hyndman 2000). Not having crossed a border, such persons did not traditionally fit in the UNHCR mandate and they did not constitute a formal category.…”
Section: Resultsmentioning
confidence: 99%
“…Physical and cognitive borders situate the internally displaced people in politically ambiguous spaces that impact the extent of humanitarian assistance they receive . They are susceptible to structural violence (Kingston and Datta ) in contested territorialities (Dean ) and exist outside of global protection norms (Cohen ). Kachin internal displacement highlights the geopolitics of international humanitarian assistance, showing how the protection role of international humanitarian organisations is circumscribed by competing claims of sovereignty; whoever controls the disbursement of aid affects its equitable distribution (Tan‐Mullins et al .…”
Section: Bordering Contested Territorialities and Affinity Tiesmentioning
confidence: 99%